Cost-Effectiveness of Posaconazole vs. First-Generation Triazoles for the Prevention of Invasive Fungal Infections Among High-Risk Patients With Hematological Malignancies in China - Shi, Changcheng; Ye, Jian; Xie, Yaping; Dong, Rong; Jin, Weizhong; Wang, Linling; Fang, Yingying; Shan, Qiyuan; Lin, Nengming (Frontiers in Public Health, 2022)
Background Posaconazole is confirmed to be more effective for preventing invasive fungal infections (IFIs) than first-generation triazoles (fluconazole and itraconazole), but its economic value has not been comprehensively evaluated in China. This study compared the cost-effectiveness of these two antifungal prophylaxis regimens in hematological-malignancy patients at high risk for IFIs from the Chinese healthcare perspective. Methods A hybrid decision tree and Markov model were built using published data to estimate the total costs and quality-adjusted life-years (QALYs) of antifungal prophylaxis with posaconazole oral suspension and first-generation triazoles. Regimens with an incremental cost-effectiveness ratio (ICER) lower than the threshold of willingness to pay (WTP) were considered cost-effective. One-way and probabilistic sensitivity analyses were performed to assess model robustness. The regional imbalance of economic development and the tablet formulation of posaconazole were considered in the scenario analyses. Results In the base-case analysis, posaconazole oral suspension provided an additional 0.109 QALYs at an incremental cost of 954.7, yielding an ICER of 8,784.4/QALY, below the national WTP threshold of 31,315/QALY. One-way and probabilistic sensitivity analyses showed that the results were robust. Scenario analyses showed that the base-case ICER was consistently below the WTP thresholds of all 31 Chinese provinces, with the likelihood of posaconazole being cost-effectiveness ranging from 78.1 to 99.0%. When the posaconazole oral suspension was replaced by the tablet formulation, the ICER increased to 29,214.1/QALY, still below the national WTP threshold and WTP thresholds of 12 provinces. Conclusions Posaconazole oral suspension is a highly cost-effective regimen for preventing IFI in high-risk hematological-malignancy patients from the Chinese healthcare perspective. Posaconazole tablets may also be considered in some high-income regions of China.